2021
DOI: 10.1093/cvr/cvab337
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β suppression dampens inflammatory leucocyte production and uptake in atherosclerosis

Abstract: Aims Targeting vascular inflammation represents a novel therapeutic approach to reduce complications of atherosclerosis. Neutralizing the pro-inflammatory cytokine interleukin-1β (IL-1β) using canakinumab, a monoclonal antibody, reduces the incidence of cardiovascular events in patients after myocardial infarction (MI). The biological basis for these beneficial effects remains incompletely understood. We sought to explore the mechanisms of IL-1β-targeted therapies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 46 publications
1
53
0
Order By: Relevance
“…At this point, anti-inflammatory treatment strategies come to play ( Figure 2 ). The IL-1β neutralizing antibody canakinumab was one of the first solely anti-inflammatory drugs shown to reduce the recurrence of cardiovascular events in high-risk CAD patients ( 374 ), and as suggested from mouse experiments, particularly does so by reducing leukocyte production in the bone marrow and deactivating EC toward less leukocyte recruitment ( 375 ). Moreover, another such highly anti-inflammatory drug, colchicine, was proven to reduce the risk of myocardial infarction, ischemic stroke, or cardiovascular death by over 25%, of note in addition to baseline treatment with lipid-lowering agents in 97% of enrolled patients ( 376 ).…”
Section: Leukocyte Recruitment In Atherosclerosismentioning
confidence: 99%
“…At this point, anti-inflammatory treatment strategies come to play ( Figure 2 ). The IL-1β neutralizing antibody canakinumab was one of the first solely anti-inflammatory drugs shown to reduce the recurrence of cardiovascular events in high-risk CAD patients ( 374 ), and as suggested from mouse experiments, particularly does so by reducing leukocyte production in the bone marrow and deactivating EC toward less leukocyte recruitment ( 375 ). Moreover, another such highly anti-inflammatory drug, colchicine, was proven to reduce the risk of myocardial infarction, ischemic stroke, or cardiovascular death by over 25%, of note in addition to baseline treatment with lipid-lowering agents in 97% of enrolled patients ( 376 ).…”
Section: Leukocyte Recruitment In Atherosclerosismentioning
confidence: 99%
“…This novel understanding is necessary when aiming at developing new anti-atherosclerotic therapies aiming at primary prevention of ASCVD, as it dictates that the inflammatory component is not only a residual risk but a risk existing throughout the development of atherosclerosis. Recent results obtained in mice with early atherosclerosis revealed that inhibition of IL-1β and NLRP3 inflammasome reduces leukocyte accumulation in atherosclerotic aortas ( 323 ). Thus, we may predict that cardiovascular interventions utilizing lowering the levels of circulating apoB-containing lipoproteins, prevention of their modifications, and reduction of the numbers of lesional macrophages already at an initial or early stage of the long subclinical asymptomatic phase of atherosclerosis may ultimately provide us the tools required for full eradication of the clinically manifest ASCVD.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…Systemic monocytosis leads to increased recruitment of macrophages to the vessel wall and the number of macrophages in the plaque correlates with plaque vulnerability: In general, the more macrophages in the plaque, the more susceptible it is to rupture ( 12 , 115 ). Systemic therapy with anti-IL1b antibodies decreases monocyte and neutrophil blood counts in experimental models and patients post myocardial infarction, and suppresses endothelial cell activation ( 54 , 116 ). Of note, in the CANTOS trial treatment with the anti-IL1b-antibody canakinumab significantly reduced rates of recurrent cardiovascular disease, independent of alterations in lipid levels ( 117 ).…”
Section: Therapeutic Approaches Targeting Macrophagesmentioning
confidence: 99%